Case of bilateral non‐traumatic subperiosteal orbital haematomas. Issue 2 (25th June 2012) - Lee, Daniel K; Tran, Phillip V; Lau, Kenneth K
Summary Subperiosteal orbital haematoma is an uncommon entity, usually unilateral and caused by trauma. We present a unique case of bilateral non‐traumatic subperiosteal orbital haematomas caused by thrombolysis and anticoagulation.